Ships / Edward V Lewis; Robert O'Brien - Lewis, Edward V.
Ships have had a profound effect on civilization. Since prehistoric times man has used them to explore, to trade and to conquer. Control has often brought their destruction. Has many ships of the present, their design, their construction and their employment.